Older Children with Torso Trauma Could Be Managed by Adult Trauma Surgeons in Collaboration with Pediatric Surgeons - Hsiang-Chieh Huang; Tzu-Chi Teng; Yung-Ching Ming; Jainn-Jim Lin; Chien-Hung Liao; Chi-Hsun Hsieh; Pei-Hua Li; Chih-Yuan Fu (MDPI AG, 2022)
Background: The purpose of this study is to assess the roles of pediatric surgeons and adult trauma surgeons in the management of pediatric torso trauma patients in a Level I adult trauma center. Methods: From 2015 to 2019, pediatric torso trauma patients (age < 18 years) were studied. A comparison between patients who did and did not undergo surgery was performed. Older children (age: 10-18 years) were compared with young adults (age: 18-35 years) selected with the same criteria using propensity score matching (PSM) and inverse probability of treatment weighting (IPTW). Results: A total of 226 patients were included in the study. Patients who underwent surgery for torso trauma (N = 61) were significantly older than patients who did not undergo surgery (N = 165) (13.1 vs. 10.4 years, p = 0.019). Both PSM and IPTW showed that the older children and young adult groups had similar proportions of patients requiring surgery (32.6% vs. 32.6%, standard difference (SD) = 0.000), proportions of patients who required torso angioembolization (8.7% vs. 9.8%, SD = 0.072), length of hospital stay (LOS) (8.1 vs. 8.0 days, SD = 0.026), and intensive care unit admission LOS (2.6 vs. 2.7 days, SD = 0.033). However, 7.1% of older children received critical care from pediatric surgeons. Additionally, 31.9% of younger children were cared for by pediatric surgeons/pediatricians. Conclusions: Adult trauma surgeons can feasibly perform surgeries for older children with torso trauma in collaboration with pediatric surgeons who provide critical care.